Agrarian reforms of Russia at the turn of the XIX–XX centuries in the coverage of economists of the XX century - I. K. Shcherbakova (Вестник университета)
The article analyses the features of the development of agriculture in Russia at the end of the 19th century - the beginning of the 20th century. The paper studies and considers attempts to solve the agrarian issue in the specified period. The study considers the course and results of the reform of 1861, as well as economic reforms of the beginning of the 20th century. The author gives an assessment of these reforms, as well as the situation of the peasantry made by the leading economists of that time: N.D. Kondrat'ev, S.L. Maslov, A.V. Peshekhonov, A.V. Chayanov, and also analyses the measures aimed at alleviating the situation of the peasantry and solving the agrarian problems of that period. The research paper also presents a comparative analysis of the consequences of the 1861 reform, its impact on the solution of the agrarian issue in different parts of the Russian Empire, in particular in Poland after the Polish Uprising of 1863.